Heterologous Boosting With Listeria-Based Recombinant Strains in BCG-Primed Mice Improved Protection Against Pulmonary Mycobacterial Infection - Liu, Si-Jing; Tian, Si-Cheng; Zhang, Yun-Wen; Tang, Tian; Zeng, Ju-Mei; Fan, Xiao-Yong; Wang, Chuan (Frontiers in Immunology, 2020)
While Baccillus Calmette-Guerin (BCG) is used worldwide, tuberculosis (TB) is still a global concern due to the poor efficacy of BCG. Novel vaccine candidates are therefore urgently required. In this study, two attenuated recombinant Listeria strains, LMΔ-msv and LIΔ-msv were constructed by deletion of actA and plcB and expression of a fusion protein consisting of T cell epitopes from four Mycobacterium tuberculosis (Mtb) antigens (Rv2460c, Rv2660c, Rv3875 and Rv3804c). The safety and immunogenicity of the two recombinant strains were evaluated in C57BL/6J mice. After intravenous immunization individually, both recombinant strains entered liver and spleen but eventually were eliminated from these organs after several days. Simultaneously, they induced antigen-specific cell-mediated immunity, indicating that the recombinant Listeria strains were immunogenic and safe in vivo. LMΔ-msv immunization induced stronger cellular immune responses than LIΔ-msv immunization, and when boosted with LIΔ-msv, antigen-specific IFN-γ CD8+ T cell responses were notably magnified. Furthermore, we evaluated the protection conferred by the vaccine candidates against mycobacterial infection via challenging the mice with 1×107 CFU of BCG. Especially, we tested the feasibility of application of them as heterologous BCG supplement vaccine by immunization of mice with BCG firstly, and boosted with LMΔ-msv and LIΔ-msv sequentially before challenging. Combination immune strategy (LMΔ-msv prime-LIΔ-msv boost) conferred comparable protection efficacy as BCG alone. More importantly, BCG-vaccinated mice acquired stronger resistance to Mycobacterial challenge when boosted with LMΔ-msv and LIΔ-msv sequentially. Our results inferred that heterologous immunization with Listeria-based recombinant strains boosted BCG-primed protection against pulmonary mycobacterial infection.